2022
DOI: 10.3389/fendo.2022.890200
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gut Microbiome and Its Metabolites, Short-Chain Fatty Acids, in Children With Idiopathic Short Stature

Abstract: BackgroundThe gut microbiome is important for host nutrition and metabolism. Whether the gut microbiome under normal diet regulate human height remains to be addressed. Our study explored the possible relationship between gut microbiota, its metabolic products and the pathogenesis of idiopathic short stature disease (ISS) by comparing the gut microbiota between children with ISS and of normal height, and also the short-chain fatty acids (SCFAs) produced by the gut microbiota.MethodsThe subjects of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
5
2
Order By: Relevance
“…In contrast to Li et al's recent study (22), which reported variations in GM composition and metabolite levels between children with ISS and the general population in eastern China, our analysis revealed no difference in microbial richness between children with ISS and their siblings. However, we did observe 3 notable variations, including the presence of Methanobrevibacter, which not only distinguished the short children from their normalheight siblings but also delineated 2 distinct subclasses within the ISS group.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to Li et al's recent study (22), which reported variations in GM composition and metabolite levels between children with ISS and the general population in eastern China, our analysis revealed no difference in microbial richness between children with ISS and their siblings. However, we did observe 3 notable variations, including the presence of Methanobrevibacter, which not only distinguished the short children from their normalheight siblings but also delineated 2 distinct subclasses within the ISS group.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, signi cant alterations in the abundance of gut microbiota were found in ISS children. The relative abundance percentages of butyrate-producing bacteria, such as Faecalibacterium and Eubacterium has been reported to be signi cantly reduced in ISS children [9]. However, our study revealed different ndings as the abundance of butyrate-producing bacteria in the gut, Butyricicoccus, Coprococcus, Fusobacterium_mortiferum, Alistipes_putredinis, and Coprococcus_comes, were reduced in ISS children.…”
Section: Discussioncontrasting
confidence: 59%
“…Recently, a study using 16S rDNA sequencing reported that the composition of gut microbiota in ISS was very different from controls, with a signi cant decrease in the butyrate-producing genera including Faecalibacterium. Targeted metabolomic analysis of fecal short-chain fatty acids from ISS children also revealed marked differences compared to healthy children [9]. In our own clinic, we observed unusual characteristics in some ISS children, including narrow food choices leading to inadequate nutrition, gastrointestinal symptoms such as constipation and sleep impairment.…”
Section: Introductionmentioning
confidence: 63%
“…Recent data have shown that microbiota-metabolites, especially SCFAs, can induce IGF-1, indicating a potential mechanism through which the microbiota may impact bone health [31]. Likewise, Li et al reported a positive correlation between SCFAs, including butyrate, and serum IGF-1 levels in the feces of children [32].…”
Section: Discussionmentioning
confidence: 99%